PENGARUH PENGGUNAAN LAYANAN ELECTRONIC BANKING TERHADAP KEPUASAN NASABAH DI DAERAH ISTIMEWA YOGYAKARTA - Evi Rosalina Widyayanti; Mudasetia Hamid (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
This study is a study that analyzes the effect of electronic banking which consists of internet banking, mobile banking and sms banking on customer satisfaction. This research was conducted in the Special Region of Yogyakarta (DIY) with 200 bank customers as respondents. This research, which was conducted with a quantitative approach, collected the results of respondent data through questionnaires distributed to 10 banks in DIY. Research analysis using Multiple Regression Analysis using SPSS analysis tool with the results β1 = 0.283, β2 = 0.398 and β3 = 0.283 then Internet Banking (X1), Mobile Banking (X2) and SMS Banking (X3) at a significance of 0.000 less than0.05 have a positive effect significant impact on Bank Customer Satisfaction in the Special Region of Yogyakarta (DIY). The F test that was carried out provided evidence that Ha was accepted which showed a mutual influence relationship between the independent variable and the dependent variable. Meanwhile, based on the summary model test, the three independent variables (free) X1, X2, and X3 indicate a positive influence simultaneously or together on Y (Customer Satisfaction). Thus, the hypothesis is proven that Electronic Banking Services consisting of Internet Banking, Mobile Banking and SMS Banking have a significant positive effect on Bank Customer Satisfaction in the Special Region of Yogyakarta.